Analysis Of Cultivation Productivity Intensive System Lele Fish In Kampung Lele Desa Kembang, Pacitan Jawa Timur District - Dzakiyah Nanda Pratiwi; David Hermawan; Budi Setyono; Ganjar Adhywirawan Sutarjo; Soni Andriawan (IJOTA (Indonesian Journal of Tropical Aquatic), 2024)
Catfish (Clarias gariepinus) farming is an important freshwater aquaculture activity that contributes to food supply and local economic development. The productivity and profitability of catfish culture are influenced by several factors, including seed quality, feed efficiency, land area, and water quality management. Therefore, this study aimed to analyze the productivity, profitability, and factors affecting catfish farming performance in Kembang Village, Pacitan Regency. The study employed a survey method by collecting primary and secondary data from catfish farmers through interviews, observations, and water quality measurements. Parameters analyzed included productivity based on land area and production cost, Feed Conversion Ratio (FCR), Return on Investment (ROI), Revenue Cost Ratio (R/C Ratio), Payback Period, Break Even Point (BEP), and water quality variables such as temperature, pH, dissolved oxygen (DO), nitrate, nitrite, and ammonia. Data were analyzed descriptively and economically to evaluate farming feasibility. The results showed that catfish farming in Kembang Village had an average productivity of 27 kg/m², with production costs reaching Rp.13,143 per kilogram of fish. The average FCR value was 1.02, indicating efficient feed utilization. The average ROI and R/C Ratio values were 14% and 1.38, respectively, demonstrating that the farming business was economically feasible. The average Payback Period was 8.20 production cycles (approximately 2.5 years). Water quality parameters generally remained within suitable ranges for catfish culture, although nitrite levels exceeded the recommended threshold. In conclusion, catfish farming in Kembang Village is economically viable, with productivity influenced mainly by seed quantity, feed management, land area, and water quality conditions.